Chemical constituents of Pestalotiopsis microspora HF 12440 - Riga Riga, Nizar Happyana, Euis Holisotan Hakim (Journal of Applied Pharmaceutical Science, 2019)
Phytochemical investigation on the liquid media of Pestalotiopsis microspora HF 12440, an endophytic fungus isolated from the stem of Artocarpus heterophyllus, led to the isolation of three lactones, (+)-acetylpestalotin (1), (−)-pestalotin (2), (6S,7S,8R)-hydroxypestalotin (3) and a lignan, (+)-pinoresinol (4). Interestingly, one of them (1) is a new compound, while compound 4 is reported for the first time from endophytic fungi. Structures of the isolated compounds were determined based on spectroscopic data, including MS, NMR 1D and 2D. Cytotoxic values of the crude extract and all isolated compounds were evaluated against P388 cells, showing that compound 3 was the most active with IC50 3.34 μg/ml. Overall, this is the first phytochemical report of endophytic fungi isolated from the host plant Artocarpus.
Keywords: Artocarpus heterophyllus, lactones, lignan, Pestalotiopsis microspora.